Penerapan Aplikasi Geogebra Terhadap Motivasi dan Pemahaman Konsep Matematika Siswa Materi Bangun Ruang Sisi Datar - Purnamasari, Risa; Supardi (Zona Education Indonesia, 2025)
This study aims to analyze the effect of using the GeoGebra application on students’ motivation and conceptual understanding of mathematics in the topic of flat-faced solid shapes. The research employed an experimental method with a pretest-posttest control group design. The sample consisted of two classes divided into an experimental group, which used GeoGebra in learning, and a control group, which applied conventional teaching methods. Data were collected through conceptual understanding tests, motivation questionnaires before and after treatment, and classroom activity observations. The results showed that the experimental group experienced a significant increase in mathematics conceptual understanding with an average n-gain of 0.65 (medium to high category), compared to the control group, which only achieved an n-gain of 0.41 (low to medium category). Additionally, the motivation of students in the experimental group increased significantly, with 78% of students reaching a high motivation category, while the control group had only 42%. Observations revealed that GeoGebra encouraged students to actively discuss, explore, and interact with the learning material. Based on these findings, it can be concluded that the application of GeoGebra is effective in improving both motivation and conceptual understanding in mathematics learning on the topic of flat-faced solid shapes. This study recommends educators to integrate visual technology-based learning tools to enhance the quality of mathematics teaching and learning processes